Torque ripple reduction in a.c. permanent magnet servo motor drives - Tang, Mi (2017)
Servo systems play an important role in industrial automation. A servo system denotes a closed loop controlled system capable of tracking required demands. One way of achieving high performance servo drive systems is to apply the closed loop control of an a.c. permanent magnet synchronous machine (PMSM). PMSM is a type of machine which rotates once three-phase a.c. voltages are supplied. The usage of permanent magnet materials contributes to the high efficiency of PMSM, and makes it a popular type of machine in industrial applications. However, the interaction between the permanent magnets and the machine stator would generate torque ripple and consequently unsmooth speed. Therefore, torque ripple of PMSM need to be considered carefully in the control of such servo systems.